Field Evaluation of Biochar Application on the Early Growth of Falcataria moluccana: Effects of Pyrolysis Temperatures and Biochar Application Rates - Wijaya, Bangun Adi; Riniarti, Melya; Hidayat, Wahyu; Prasetia, Hendra; Yoo, Jiho; Park, Byung Bae (Jurnal Sylva Lestari, 2025)
Faltacaria moluccana at its early plantation, is devastated by heat and water stress due to current global climate change. Production forests in Indonesia suggested to use biochar to enhance the durability of early growth F. moluccana in the field. Empty fruit bunches (EFB), a gigantic abundant waste material in Indonesia, pose its potential as biochar feedstock. This study aims to evaluate the effects of EFB biochar on the growth of F. moluccana for one year in a field setting. The experiment used two biochar application rates (25 and 50 tons/ha) and biochar produced at two pyrolysis temperatures (400°C and 600°C). Climatic factors (rainfall and average temperature) were monitored to assess how biochar interacted with field conditions to influence the growth of F. moluccana. EFB biochar increased height and diameter increment by up to 25% and 42%, respectively, compared to control after one year. While pyrolysis temperatures show no impact on growth, biochar application rates of 25 and 50 tons/ha significantly boost diameter increments by 36% and 42%, respectively, compared to controls, without affecting height. Biochar also improves monthly growth increments under water and heat stress. EFB biochar optimizes growth under current climate conditions in Indonesia and mitigates the negative effects of extreme temperature fluctuations. Keywords: biochar, early plant growth, empty fruit bunch, Faltacaria moluccana, field experiment